Thucydides and Pindar : historical narrative and the world of Epinikian poetry - Hornblower, Simon (Oxford University Press, 2006)
Thucydides was one of the greatest of the ancient Greek historians and Pindar one of the greatest Greek poets, specializing in celebratory odes for victors in the great games - above all at Olympia. Simon Hornblower puts these two towering figures side-by.